2018
DOI: 10.1007/s00268-018-4784-6
|View full text |Cite
|
Sign up to set email alerts
|

The Unacceptable Morbidity of Negative Laparoscopic Appendicectomy

Abstract: The morbidity of negative LA is the same as LA for uncomplicated appendicitis. The morbidity of LA for complicated appendicitis is significantly higher. The selection criteria for LA in our unit needs to be reviewed to address the high negative appendicectomy rate and avoid unnecessary surgery and its associated morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 100 publications
0
32
0
1
Order By: Relevance
“…The authors reported an overall negative appendectomy rate of 36.0% among 1413 patients who met inclusion criteria (904 in the positive group and 509 in the negative group). Morbidity rates (6.3% vs 6.9%; P = 0.48) and types of morbidity were the same for negative appendicectomy and uncomplicated AA, and there was no significant difference in complication severity or length of stay (2.3 vs 2.6 days; P = 0.06) between negative appendicectomy and uncomplicated AA groups [200].…”
Section: Q47: Does Aspiration Alone Confer Clinical Advantages Overmentioning
confidence: 85%
“…The authors reported an overall negative appendectomy rate of 36.0% among 1413 patients who met inclusion criteria (904 in the positive group and 509 in the negative group). Morbidity rates (6.3% vs 6.9%; P = 0.48) and types of morbidity were the same for negative appendicectomy and uncomplicated AA, and there was no significant difference in complication severity or length of stay (2.3 vs 2.6 days; P = 0.06) between negative appendicectomy and uncomplicated AA groups [200].…”
Section: Q47: Does Aspiration Alone Confer Clinical Advantages Overmentioning
confidence: 85%
“…Detailed analysis of the indications, findings and outcomes have been previously published. 8 There were 42 (0.9%) patients with post-appendicectomy IAA that comprised this cases series. Sixteen (38.1%) had large (> 4 cm) IAAs that were managed with a percutaneous drainage.…”
Section: Resultsmentioning
confidence: 97%
“…1,[4][5][6]35,36 One explanation is the high negative appendicectomy rate (36%) during the study period. 8 As IAA is more commonly associated with complicated appendicitis compared with uncomplicated appendicitis [4][5][6] but has a similar incidence for uncomplicated appendicitis and a normal appendix, 8 this is less likely to be the sole explanation. Another explanation is the use of laparoscopic washout in 41 (0.8%) patients with persistent evidence of sepsis following appendicectomy during the study period 37 that may have resulted in the prevention of the subsequent development of an IAA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations